PERSEPSI WIRAUSAHAWAN DI PASAR MENGENAI PENTINGNYA MELANJUTKAN SEKOLAH ANAK KE PENDIDIKAN TINGGI - Farichi, Mohammad Achsinul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
Perception is a process of delivering relevant information captured by the senses of the environment which then organizes it in its mind, interprets, experiences, and processes everything that happens in that environment. The factors of perception are a process of delivering relevant information captured by the senses of the situation, set, attention, value system, previous experience, selective attention. University is the level of education after secondary education, which includes diploma education programs, graduate, master, specialist, and doctorate, which are organized by the university. This research was conducted in an effort to reach the research objectives, namely: (1) To explain the perception of the entrepreneur in the Gudang Garam market Unit 8 Kediri city about the importance of continuing school children to university. This research uses qualitative approach and descriptive type, data collection is done by using the method of observation, interview, and documentation. Then the data has been collected in the form of words analyzed with Miles Huberman model. The results showed that: (1). An entrepreneur assumes continuing education of children to university is very important, (2). Entrepreneur send their children to university have hope that the children have a better future from than their parents, the goal is achieved, can become government employees or become civil servants and add insight to the knowledge of his son and as a bridge to achieve success in the future, (3 ). Past entrepreneur experiences greatly affect the entrepreneur’s perception of continuing his or her child's education to university as experienced by some traders, (4). Entrepreneurs have figures who influence their perceptions in educating their children.Keywords: Perception, Entrepreneur, University.